Allopontonia alastairi sp. nov., a second species of the genus Allopontonia Bruce, 1972 (Crustacea: Decapoda: Pontoniinae), from the Australian Northwest Shelf - Bruce, A. J. (Zootaxa, 2010)
The pontoniine genus Allopontonia Bruce, 1972 has so far been represented by only a single species, A. iaini Bruce, 1972, a shallow water echinoderm associate (Bruce, 1972). First described from Zanzibar, it is one of the relatively few pontoniine species found in both the Indo-West Pacific and the Eastern Pacific regions (Wicksten 2000; Bruce 1987). The discovery of a second species is therefore of interest and an illustrated description is here provided. The single specimen was collected in the course of a CSIRO Marine and Atmospheric Research (CMAR) survey of the benthic fauna of the Australian Northwest Shelf region, Western Australia, by the fisheries research vessel Southern Surveyor and is held in the collection of the Museum Victoria. I am most grateful to Anna McCallum for the opportunity to study this specimen. Felicity McEnnulty provided the identification of the host echinoid.